The Role of Interdisciplinary Collaboration in Preventing Hospital-Acquired Infections Strategies for Reducing Healthcare-Associated Infections (HAIs): A Systematic Review - M Alwahbi, Mohammed Mosa; Aljasir, Ahmed Ibrahim Abdullah; Alanazi, Naif Kassab Suwaylim; O Alharbi, Saleh Abdullah; Yahya Hakmy, Lamya Mohammed; Saleh Albusayli, Sami Ibrahim; Alhazzaa, Thamer Abdullah Ibrahim; Alharbi, Mohammed Salem Marzouq (Journal of Neonatal Surgery, 2025)
Hospital-acquired infections (HAIs) are a significant problem for healthcare systems around the world because they raise morbidity, mortality, and costs. Through cooperative infection control initiatives, this research examines the roles played by different healthcare workers in lowering HAIs. Physiotherapists, radiologists, dentists, operating room technicians, pharmacists, Specialist-Sociology, Technician-Respiratory Therapy , Technician-Radiological Technology, Technician-Laboratory, Technician - Health Informatics and nurses all play essential roles in promoting antimicrobial stewardship and implementing infection prevention strategies. By adhering to protocols, including good hand hygiene, sterilization methods, and prudent use of antibiotics, these personnel help reduce the spread of diseases in hospital environments. Infection control bundles and antibiotic stewardship initiatives are examples of interprofessional teamwork that further improves patient safety and healthcare results. To prevent HAIs, healthcare professionals' diverse areas of expertise must be acknowledged and integrated, as this research demonstrates.and previa. Majority of the mothers had recovered, while, a few had to be admitted to the ICU whereas some of them passed away. Various maternal outcomes included postpartum hemorrhage, peripartum hysterectomy and blood transfusion. Perinatal outcomes included preterm birth, still birth, NICU admission and death